At the Origins of Classical Opera : Carlo Goldoni and the «dramma Giocoso per Musica». - Rista, Pervinca (Bern : Peter Lang AG International Academic Publishers, 2018)
Perhaps because of his stature and influence as a comic playwright, Goldoni has rarely been considered as an innovator in the musical sphere. This study aims to shed new light on his primary role in the evolution of Classical opera, and on the legacy of his innovations in the European musical tradition.
Cover -- Table of Contents -- Preface -- Introduction -- I. The other Goldoni -- i. "State of the art" -- II. The foundations of musical comedy -- i. The limits of opera seria -- ii. Naples and the commedia per musica -- iii. Venice and the intermezzo -- III. New directions -- i. Goldoni's apprenticeship with musical texts -- ii. New directions for comedy -- iii. A new art for a new society: the dramma giocoso takes shape in Venice -- IV.  A new source for Classical opera: Goldoni's drammi giocosi -- i. The real world -- ii. The mezzo carattere -- iii. Buffo, serio, and the space between -- V. How comedy changed opera -- i. The musical elements of comedy -- ii. Comedies that became drammi giocosi -- iii. Goldoni as musical reformer -- VI. Goldoni's Musical Legacy -- i. Globalization? Old news! International drammi giocosi and diffusion of a new genre -- ii. Mozart and Goldoni -- iii. Conclusions.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books